2020
DOI: 10.2147/ott.s255195
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA <em>TBX5-AS1</em> Regulates the Tumor Progression Through the PI3K/AKT Pathway in Non-Small Cell Lung Cancer</p>

Abstract: Long non-coding RNAs (lncRNAs) have been reported to play important roles in tumor biology. In this study, we aimed to investigate the effects of T-box transcription factor 5 antisense RNA 1 (TBX5-AS1) on aggressive phenotypes of non-small cell lung cancer (NSCLC) cells and explore its regulatory pathway. Methods: The expression of TBX5-AS1 in tissues, plasma, and cells was determined by qRT-PCR. Cell viability, proliferation, migration, invasion, and apoptosis were assessed using MTT, colony formation, wound-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Although it has been reported lncRNA TBX5-AS1 as antisense RNA of TBX5 could serve as potential diagnostic biomarkers for NSCLC and could inhibit the tumor progression of NSCLC through inactivating the PI3K/AKT pathway [27][28][29], the exact mechanism between TBX5-AS1 and TBX5 in LUAD has not been reported and there are no studies used eRNA as a biomarker for LUAD. In this study, we performed a comprehensive data analysis approach and found that TBX5-AS1 belong to a subclass of lncRNAs, termed "enhancer RNA".…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported lncRNA TBX5-AS1 as antisense RNA of TBX5 could serve as potential diagnostic biomarkers for NSCLC and could inhibit the tumor progression of NSCLC through inactivating the PI3K/AKT pathway [27][28][29], the exact mechanism between TBX5-AS1 and TBX5 in LUAD has not been reported and there are no studies used eRNA as a biomarker for LUAD. In this study, we performed a comprehensive data analysis approach and found that TBX5-AS1 belong to a subclass of lncRNAs, termed "enhancer RNA".…”
Section: Discussionmentioning
confidence: 99%
“…The potential functions of the five genes may partially contribute to the prognostic prediction, but the underlying mechanisms upon these genes in GBM remains to be investigated (34)(35)(36). Of the five lncRNAs, apart from TBX5-AS1, which has been to reported be related with unfavorable prognosis in non-small-cell lung carcinoma (NSCLC) (37,38), the other four has never been explored in cancer, and none of them has ever been explored in GBM. In this case, we believe that it is promising to explore the potential mechanisms of these genes (especially the TBX5-AS1 which acts as a risk factor in our model) related to GBM.…”
Section: Discussionmentioning
confidence: 99%
“…To further develop a novel prognostic model based on eRNAs, we screened an eRNA and focused on TBX5-AS1. Previously, TBX5-AS1 has been discovered to participate in the tumorous development of several cancers, including LUAD [ 16 , 25 , 26 ]. In addition, its dysregulation was also reported.…”
Section: Resultsmentioning
confidence: 99%